Case report: A case of Culler-Jones syndrome caused by a novel mutation of GLI2 gene and literature review - Zhang, Yiwen; Dong, Bingzi; Xue, Yu; Wang, Yunyang; Yan, Jing; Xu, Lili (Frontiers in Endocrinology, 2023)
Culler-Jones syndrome is a rare clinical phenomenon with diverse manifestations and is prone to misdiagnosis. We report one patient who presented with a 10-year history of anosmia and a 1-year history of epididymal pain. Kallmann syndrome was suspected initially. The results of his laboratory tests, imaging, and genetic testing, however, combined to provide a conclusive diagnosis of Culler-Jones syndrome. With the aid of high-throughput sequencing technology, the GLI2 gene c.527A>G (p.Tyr176Cys) heterozygous mutation in the child was identified. No published works have yet described this mutation site. We described Culler-Jones syndrome in a child at length. We recommend that Culler-Jones syndrome be taken into account when considering the spectrum of disorders associated with abnormal growth and development in children. Once diagnosed, individualized hormone replacement treatment is required for each patient.